Complex depression: The treatment of major depression and severe personality pathology. Issue 5 (17th February 2019) - Clarkin, John F.; Petrini, Mark; Diamond, Diana
Abstract: The intensive treatment of a patient presenting with major depression, chronic suicidal ideation, and a borderline personality disorder with narcissistic features is described as it developed over an 18‐month treatment. The treatment approach is a transdiagnostic one with an emphasis on change in the patient's representation of self and others, identity and interpersonal functioning. The intended change is not only in the reduction of depression and suicidal ideation but also an improvement in interactions with others at work and intimate relations. The combination of rich clinical information from the therapist and independent research ratings of patient progress provide a complex picture of the treatment.